Penempatan Green Point Sebagai Edukasi Publik Dalam Pembuangan Sampah - Ongah, Harun; Shara, Yuni (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2025)
Indonesia's rapid population growth has led to an increase in waste volume, yet only 63.3% is adequately managed. A primary obstacle in waste management is the low level of public literacy and limited access to sorting facilities. This community service project aims to enhance public education and facilitate inorganic waste disposal through the implementation of Green Points. The method involved a strategic collaboration between academics, PT Bank Central Asia Tbk. (BCA), and the Buddhist Tzu Chi Foundation Indonesia, Medan Branch. Facilities were strategically placed across three of BCA’s largest branches in Medan in 2020, 2021, and 2024, complemented by socialization sessions for nearly 100 employees. The results indicate a significant increase in participants' awareness and understanding regarding the importance of waste segregation at the source. The presence of Green Points as a visual education medium successfully transformed waste disposal behavior in the corporate environment, as evidenced by the consistent volume of recycled materials collected. This program recommends replicating similar partnership models in other institutions to expand the impact of community-based waste management.